THE USE COOPERATIVE LEARNING METHOD IN IMPROVING STUDENTS' WRITING ABILITY(A Classroom Action Research at One of Senior High School in Cinajur) - Wulan Khaerunisa, - (2011)
Abstract This research investigated the use of cooperative learning method in students' writing ability. The research was conducted to find out whether cooperative learning method improved students' writing ability or not, and to find out students' response toward cooperative learning method. The research design employed in this research was Classroom Action Research which consisted of four main steps: planning, acting, observing, and reflecting, conducted in three cycles. The study was conducted at XI Grade of science programs which comprised thirty students. Observation checklist, students' journal, evaluation sheet and students' writing score were used as instruments to collect the data. The students' writing tests were scored on the basis of analytical scoring format for analytical exposition writing adapted from Cohen, et al. (1994). The study was considered successful if the degree of the students' writing score throughout the implementation of the method achieved MMC; it was 75. The findings of the study showed that cooperative learning method improved students' writing ability in analytical exposition text. In the first cycle, there were 20% of students who passed the test, while in cycle 2, the students still did not reach Minimum Mastering Criteria (MMC) or Kriteria Ketuntasan Minimal (KKM). In the third cycle, all of the students were be able to get MMC. It can be inferred, therefore, that cooperative learning method can improve the students' writing ability, especially in analytical exposition text. It can be seen from students' score improvement in their writing composition. It is finally suggested that the teachers use cooperative learning method in teaching writing, especially in analytical exposition texts. The other researchers are invited to conduct further research based on the findings of this study to develop better method in the teaching of writing.